A new method for forming a comprssion enteric anastomosis for acute mesenteric ischemia - O. N. Botsula; G. Th. Dambayev; M. M. Soloviyov; A. M. Popov; V. E. Gyunter; A. N. Baikov; M. A. Sharayevsky (Бюллетень сибирской медицины)
In experiment on 20 mongrel dogs demonstrated the possibility of forming a comprssion enteric anastomosis in acute mesenteric ischemia using nikelid-titanium implants. In order to control vascularisation anastomosises sites it is applied transilluminations angioscopy. Determined by mechanical strength and terms of an inconsistency anastomosises, terms of tearing away of a design are defined. Carrying out possibility keeping bodies operations on a small intestine and character of healing anastomosis as a primary tension is proved.